The effect of different types of exercise on sleep quality and architecture in Parkinson disease: a single-blinded randomized clinical trial protocol - Cristini, Jacopo; Potvin-Desrochers, Alexandra; Seo, Freddie; Dagher, Alain; Postuma, Ronald B; Rosa-Neto, Pedro; Carrier, Julie; Amara, Amy W; Steib, Simon; Paquette, Caroline; Roig, Marc (Physical therapy & rehabilitation journal, 2024)
The purpose of this trial is to (1) determine the best exercise modality to improve sleep quality and sleep architecture in people with Parkinson disease (PD); (2) investigate whether exercise-induced improvements in sleep mediate enhancements in motor and cognitive function as well as other non-motor symptoms of PD; and (3) explore if changes in systemic inflammation after exercise mediate improvements in sleep.This is a multi-site, superiority, single-blinded randomized controlled trial. One hundred fifty persons with PD and sleep problems will be recruited and randomly allocated into 4 intervention arms. Participants will be allocated into 12 weeks of either cardiovascular training, resistance training, multimodal training, or a waiting list control intervention. Assessments will be conducted at baseline, immediately after each intervention, and 8 weeks after each intervention by blinded assessors. Objective sleep quality and sleep architecture will be measured with polysomnography and electroencephalography. Motor and cognitive function will be assessed with the Unified PD Rating Scale and the Scale for Outcomes in PD-Cognition, respectively. Subjective sleep quality, fatigue, psychosocial functioning, and quality of life will be assessed with questionnaires. The concentration of inflammatory biomarkers in blood serum will be assessed with enzyme-linked immunosorbent assays.This study will investigate the effect of different types of exercise on sleep quality and architecture in PD, exploring interactions between changes in sleep quality and architecture with motor and cognitive function and other non-motor symptoms of the disease as well as mechanistic interactions between systemic inflammation and sleep. The results will provide important practical information to guide physical therapists and other rehabilitation professionals in the selection of exercise and the design of more personalized exercise-based treatments aimed at optimizing sleep, motor, and cognitive function in people with PD.
Online veröffentlicht: 24. Juni 2023
Gesehen am 25.06.2025